Boundedness, Rate of Convergence and Global Behavior of a Higher-Order System of Difference Equations - Khan, Dr. Abdul Qadeer; Razzaq , Waseem (Sarajevo Journal of Mathematics, 2026)
In this paper, we conduct a comprehensive exploration of the dynamical characteristics of a higher-order non-symmetric system of difference equations. Our investigation covers various fundamental aspects, including the existence of equilibria, persistence, periodic points, boundedness, local behavior at equilibria, convergence rate, and global dynamics. Our results significantly extend and improve upon existing findings in the literature. Finally, theoretical findings are illustrative numerically.